Earning Inequalities in Pakistan: Is Education the Main Driver? - Muhammad Idrees; Farzana Naheed Khan (NUST Journal of Social Sciences and Humanities)
The present study is an attempt to explore the role of education in earning inequalities. The analysis is based on two surveys of HIES for 2010-11 and 2015-16. Overall, the earning inequalities in Pakistan and its rural-urban segments are decomposed with respect to the education of the earner. For this purpose, the earners are classified into eight education groups. The results show that significant number of earners are either illiterate or belong to low education groups. Moreover, the level of inequality in general reduces with the increase in education level. Therefore, expansion of higher education can be a source of reducing earning inequality and hence, promoting more fair distribution of income and consumption. However, the study finds that around 20% of earnings inequalities are explained by differences in education in Pakistan. Therefore, the main conclusion of the present study is that contrary to the expectations, education of the earners does not account for much of the inequality among earnings and further studies are needed to analyze this phenomenon.